Cooperative Design, Visualization, and Engineering 8th International Conference, CDVE 2011, Hong Kong, China, September 11-14, 2011. Proceedings - Luo, Yuhua; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 8th International Conference on Cooperative Design, Visualization, and Engineering, CDVE 2011, held in Hong Kong, China, in September 2011. The 33 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers address all aspects of distributed computing, and were organized in topical sections on cooperative design, cooperative applications, cooperative engineering, cooperative visualization, and basic theory and technology.
Keywords: Computer science; Computer Communication Networks; Software engineering; Information storage and retrieval systems; Information systems; Computer Science; Computer Communication Networks; Information Systems Applications (incl.Internet).; Software Engineering; User Interfaces and Human Computer Interaction; Information Storage and Retrieval; Computers and Society